Spectroscopic and computational investigation of the structure and pharmacological activity of 1-benzylimidazole. Issue 6 (1st November 2017) - Madanagopal, A.; Periandy, S.; Gayathri, P.; Ramalingam, S.; Xavier, S.; K. Ivanov, Vladimir
Abstract: The chemical and pharmacological activity of the compound 1-benzylimidazole was analysed using vibrational, NMR and UV-Visible spectroscopic tools. The necessary data were obtained by recording FT-IR, FT-Raman, NMR and UV-Visible spectra. 1 H and 13 C NMR spectral chemical shifts were observed and investigated to understand the basis of the antiparasitic, antifungal and antimicrobial activities. The elaborate electronic excitational absorptions in which bathochromic shifts in the UV-Visible spectrum are linked to strong cardiotonic activity are noteworthy. The pharmacodynamic activity was related to the molecular polarization as analysed according to different analytical parameters. The molecular reactivity was studied according to the dislocation of charge levels in frontier molecular orbitals. NBO analysis was carried out to delineate the asymmetric charge interaction transitions among orbitals, which were correlated with the pharmacological behaviour of the compound. The enantiomer errors in the electronic structure have been analysed by simulating ECD and VCD spectra.